Shakespearean Legal Thought in International Dispute Settlement. (28th February 2018) - Schultz, Thomas; Ost, François
ABSTRACT: In this article, the authors examine the contributions of Shakespearean legal thought to our understanding of core aspects of international dispute settlement. These aspects include: the sweeping role of masks in law and in the resolution of disputes; the construction and deconstruction of authority; the purpose of law in arousing desire and thus action; the limits in recognizing informal international law as law; the benefits of exaggeration; the problematic ambition of adjudicators; the key role of passion, against rationality, in understanding and dealing with international disputes; the decision-making resources to be found in logics of life; exercising measure in the enforcement and reach of law; remembering that law deals with human beings in our quest for law's purity and systematic organization; resisting single-mindedness; the relevance of a dialectic form of proportionality; and the inescapable need to embrace uncertainty. The authors also discuss the general relevance of law and literature, and law and theatre, for all manner of legal professionals and review Shakespeare's own legal background and thus his a priori ability to deal with legal matters.